2010
DOI: 10.4236/msa.2010.13021
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Contamination of Surface Soil in Relationship to Land Use Patterns: A Case Study of Benue State, Nigeria

Abstract: A detailed investigation was conducted on the relationship between land use patterns and trace metal content in surface soils of the Benue State to assess soil environmental quality. Results revealed that metals levels were generally high in mineralized and urban soils and lower in agricultural soils whilst forest soils were lease by anthropogenic pollution. Mineralized soils developed from weathered sulphides were rich in lead (Pb), zinc (Zn), and cadmium (Cd). Urban soils accumulated copper (Cu), Zn, and Cd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…Long term use of agrochemicals such as fertilizers and pesticides (insecticides, herbicides and fungicides) to increase crop yield often contribute to HM pollution because of their composition and soil characteristics. In a past study, the high concentrations of As, Pb, and Cd in agricultural soils were attributed to the application of agrochemicals [26]. A previous study has also shown that copper based fungicides have the potential to increase concentration of Cu in the soil to phytotoxic levels [27].…”
Section: Sourcesmentioning
confidence: 99%
“…Long term use of agrochemicals such as fertilizers and pesticides (insecticides, herbicides and fungicides) to increase crop yield often contribute to HM pollution because of their composition and soil characteristics. In a past study, the high concentrations of As, Pb, and Cd in agricultural soils were attributed to the application of agrochemicals [26]. A previous study has also shown that copper based fungicides have the potential to increase concentration of Cu in the soil to phytotoxic levels [27].…”
Section: Sourcesmentioning
confidence: 99%
“…According to Pearson correlation analysis between Cd and Zn concentrations in three different land uses, significant positive correlation (p<0.05) was found for non-agricultural soils (r = 0.49). Strong correlations between elements imply similar geochemical controls in the surface environment (Adamu & Nganje, 2010). Luo et al (2007) also reported that metals which are poorly correlated with other metals have different sources of origin.…”
Section: And Zn Concentrations Of Different Land Usesmentioning
confidence: 96%
“…Anthropogenic activities change the natural concentrations of soil trace metals in different land use types with varying magnitudes. Knowledge of metal concentrations for different land use types is of critical importance in assessing human impact on metal concentrations in soils and also in land use planning (Adamu & Nganje, 2010). There have been several studies on accumulation of trace metals in soils under different land uses in Sri Lanka.…”
Section: Introductionmentioning
confidence: 99%
“…Selected environmental pollution indexes for water samples 'Heavy Metal Evaluation Index (HEI) of the Groundwaters' [6], as for soil samples 'Mobility of Metals' [7], 'Single-Factor and Composite Pollution Index of Soils' [8], Anthropogenic Factor (AF) [9] and 'Enrichment Factor (EF) Indexes of Soil' [10], 'Potential Ecological Risk Factor Indexes' [11], and as for plant samples 'Heavy Metal Transfer (Bioconcentration) Factor' and 'Target Hazard Quotient (THQ) of Food' [12] were used for comprehensive and integrated evaluation of parameters.…”
Section: Fig 1 Map Of Greenhouse Regions Of Gazipaşamentioning
confidence: 99%